The development of position-specific performance indicators in professional rugby union - James, N.; Mellalieu, S. D.; Jones, N. M. P. (Journal of Sports Sciences, 2005)
The aim of this study was to construct a valid and reliable methodology for the analysis of performance profiles of individual playing positions within rugby union. Twenty-two matches were sampled from the domestic season of a professional male rugby union team. Key performance indicators for individual positions were developed and notated using a computerized behavioural analysis system. Performance profiles of playing positions containing data from one or more individuals were then constructed to compare intra-positional differences. Significant differences (chi-square) were observed between individuals within all the tested playing positions for the principal performance indicators (passing, carrying and tackling for the forward positions, and passing, carrying, tackling and kicking for the backs). For example, the difference between the two outside-halves in the study (P?<?0.001) was illustrated by one of the players having a median of 6 successful carries for the season (95% confidence limits of 13 and 3), whereas the other had a median of 2 successful carries (95% confidence limits of 5 and 1). The findings suggest that while general positional performance profiles appear to exist, intra-positional differences may occur due to variations in an individual's style of play, the decision-making demands of the position and the effects of potential confounding variables. Multiple profiles may therefore be necessary for some playing positions to account for variation in factors such as playing conditions and the strength of the opposition.